Is gold dinar the appropriate money in Islam? - Santoso, Bedjo; Mydin Meera, Ahamed Kameel; Ahmad, Khaliq (IIUM Press, 2018)
The idea of revisiting currency and gold dinar from an Islamic standpoint as done in this paper is an interesting discourse in the current monetary system. The literature survey included historical aspect, supremacy of gold currency and the weakness of fiat money by employing maslahah-mursalah approach. The law of gold, as money, from Maqasid al-Shari’ah and Siyasah Syar’iyya approaches were discussed. The paper deliberated on some possible alternative forms of gold as money and then evaluated some obstacles and barriers in the hope of finding the best model of gold as money to be implemented in the current economic system. Deductive method is utilized to explore the implementation of gold currency based on historical study and library research. The findings revealed that, money is not limited to gold and silver. However, by using derivation from based on process from sources of law-making, the ‘hukm’ of gold/silver as money is permissible. While, the hukm for the country to mint gold dinar is subject to change into wajib, if the objective is to protect nation and people from harm. Maqasid al-Shari’ah and maslahah-mafsadah studies have also strengthened the view. Moreover, the review indicated that gold as money serves maslahah while fiat money serves more mafsadah. However, it is difficult to implement gold dinar monetary system in the current system due to some impediments. Backed by information/communication technology and adequate political will, gold may, however be employed as measurement of value; and as such could be implemented in certain communities including cooperatives....